Takut akan Tuhan sebagai Awal Kebijaksanaan: Kepemimpinan Kristiani menurut Amsal 1:7 - Bala, Gabriel (Felicitas, 2023)
True Christian leadership comes from the Lord Jesus Himself. In Jesus, a Christian leader will lead the people entrusted to him with values and virtues that come from God himself. One of those values and virtues is the "fear of the Lord". Proverbs itself says that the "fear of the Lord" is the beginning of wisdom (1:7). Wisdom itself is one of the virtues that a leader must possess. Thus, if one wants to be a wise leader, then there must be the "fear of the Lord" within him. With this "fear of the Lord", a Christian leader will try to involve God in every decision. He will think about whether his decisions are good for everyone or not. In this article, the author will explore the spirit of Christian leadership according to Proverbs 1:7. What kind of "fear of the Lord" is meant in this book and how to apply it in daily life, so that this "fear of the Lord" can also become the spirit and spirit of Christian leaders.